Microbial burden and inflammasome activation in amniotic fluid of patients with preterm prelabor rupture of membranes - Theis, Kevin R. (J Perinat Med, 2020)
INTRODUCTION: Intra-amniotic inflammation, which is associated with adverse pregnancy outcomes, can occur in the presence or absence of detectable microorganisms, and involves activation of the inflammasome. Intra-amniotic inflammasome activation has been reported in clinical chorioamnionitis at term and preterm labor with intact membranes, but it has not yet been investigated in women with preterm prelabor rupture of membranes (preterm PROM) in the presence/absence of detectable microorganisms. AIM: To determine whether, among women with preterm PROM, there is an association between detectable microorganisms in amniotic fluid and intra-amniotic inflammation, and whether intra-amniotic inflammasome activation correlates with microbial burden. METHODOLOGY: Amniotic fluids from 59 cases of preterm PROM were examined for the presence/absence of microorganisms through culture and 16S rRNA gene qPCR, and concentrations of interleukin 6 (IL-6) and ASC (apoptosis-associated spec-like protein containing a CARD), an indicator of inflammasome activation, were determined. RESULTS: qPCR identified more microbe-positive amniotic fluids than culture. Greater than 50% of patients with a negative culture and high IL-6 concentration in amniotic fluid yielded a positive qPCR signal. ASC concentrations were greatest in patients with high qPCR signals and elevated IL-6 concentrations in amniotic fluid (i.e. intra-amniotic infection), and ASC concentrations tended to increase in patients without detectable microorganisms but yet with elevated IL-6 concentrations (i.e. sterile intra-amniotic inflammation). CONCLUSION: qPCR is a valuable complement to microbiological culture for the detection of microorganisms in the amniotic cavity in women with preterm PROM, and microbial burden is associated with the severity of intra-amniotic inflammatory response, including inflammasome activation.